Cerebrovascular Function in Hormonal Migraine: An Exploratory Study - Dzator, Jemima S. A.; Howe, Peter R. C.; Griffiths, Lyn R.; Coupland, Kirsten G.; Wong, Rachel H. X. (Frontiers in Neurology, 2021)
Background: Migraineurs, particularly young premenopausal women, are at increased risk of cerebrovascular disease; however, there is currently limited evidence as to whether hormonal migraine is associated with poor cerebrovascular function. Objectives: The objectives of this study were to: (1) investigate the potential association of cerebrovascular function with hormonal migraine and (2) determine whether abnormalities of cerebrovascular function in hormonal migraineurs are associated with migraine-related disability and/or quality of life. Method: A cross-sectional study was undertaken in 50 hormonal migraineurs (mean age: 38.7 ± 1.2 years) and 29 controls (mean age: 35.6 ± 1.8 years). Data were collected at a single point in time from all participants during the inter-ictal period when they were free from migraine and not menstruating. Transcranial Doppler ultrasound was used to measure resting blood flow velocity and cerebrovascular responsiveness (CVR) to hypercapnia and cognitive stimulation (neurovascular coupling) in the left and right middle cerebral artery (MCA). Additionally, hormonal migraineurs completed three questionnaires to assess migraine-related disability and quality of life as well as migraine frequency and intensity: Headache Impact Test-6™, Migraine-Specific Quality of Life and Migraine Disability Assessment. Results: Hormonal migraineurs had lower resting mean blood flow velocity (MBFV) (P = 0.009) and neurovascular coupling during cognitive stimulation (P = 0.010) in the left MCA than controls. No such differences were found in the right MCA. Additionally, heart rate (P = 0.004) was higher in hormonal migraineurs than controls. However, no differences in CVR to hypercapnia were found between hormonal migraineurs and controls. Multi-variate analysis revealed age to be a significant (P = 0.012) predictor of MBFV in the left MCA. Negative correlations between headache frequency and CVR to hypercapnia in the left (P = 0.026) and right MCA (P = 0.044) were found. Additionally, negative correlations between neurovascular coupling during the 2-Back 1.5 s task in the right MCA and the MSQoL emotional (P = 0.013) and role-function restrictive (P = 0.039) domains were found. Conclusions: This is the first study to show that hormonal migraineurs have poorer cerebrovascular function, as represented by lower resting MBFV and impaired neurovascular coupling in the left MCA. Future studies should investigate whether improving cerebrovascular function can prevent hormonal migraine and improve quality of life. Clinical Trial Registration: ACTRN12618001230246.